Conjoint application of bio-organic and inorganic nutrient sources for improving cropping behaviour, soil properties and quality attributes of apricot (Prunus armeniaca) - SINGH, V J; SHARMA, SOM DEV; KUMAR, PRAMOD; BHARDWAJ, SATISH KUMAR; RAJ, HARENDER (The Indian Journal of Agricultural Sciences, 2010)
The study was carried out during 2006–08 on 20-year-old ‘New Castle’ apricot (Prunus armeniaca L.) trees to investigate the conjoint efficacy of bio-organics used along with chemical fertilizers on cropping behaviour, soil properties and quality attributes. Conjoint application of biofertilizers 60 g/tree, vermicompost 30 kg/tree, cow urine 12.5% and 50% NPK resulted in significantly maximum bloom density (25.08%), fruit set (62.38%), yield (29.85 kg/tree), fruit firmness (7.06 kg/cm2), total soluble solids (17.04 °Brix), reducing sugars (3.97%), ascorbic acid (7.29 mg/100 g) and total carotenoids (0.96 mg/100 g). This combination also significantly improved physical, chemical and biological properties of the soil rhizosphere. Available N, P and K content of rhizosphere soil was increased by 34.8, 88.3 and 16.6%, respectively. Micronutrients (Fe, Cu, Zn, Mn) were improved by 15.1, 25.3, 28.7 and 24.1% respectively. The microbial biomass pool in terms of Pseudomonas, Bacillus, Azotobacter chroococcum and Arbuscular mycorrhizal fungi increased by 208.25, 113.40, 383.50 and 442.50% respectively over control.